Implementing The Anti-Money Laundering Law: Optimizing Asset Recovery in Corruption Cases in Indonesia - Yoserwan, Yoserwan; Dias, Fausto Soares (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Corruption is still a severe problem in Indonesia. In 2022, the Attorney General Office of the Republic of Indonesia alone succeeded in handling 405 of 597 corruption cases in 2022, with a state loss of 39.207 trillion out of a total of 42.747 trillion. When the state loss is combined with the state economic loss, which refers to the indirect financial impact on the state due to corruption, the number will be up to IDR142 trillion. However, the total asset recovery through fines and state loss compensation was only IDR 8.9 trillion. Thus, it only recovers about 12% of state losses due to corruption. One of the efforts to recover state losses is applying the law on money laundering because its main objective is to pursue the proceeds of a crime, including corruption. This paper discusses how the money laundering law will be more optimal in recovering state losses due to corruption and its application in several cases. The method used in this study is normative legal research, especially case studies relating to implementing a money laundering law on corruption cases. From the study, it can be concluded that the anti-money laundering law was not optimally applied in asset recovery in corruption cases. Only in corruption, which indicates an actual state loss, can the anti-money laundering law be applied. Moreover, there should also be an indication that the money laundering process follows corruption. Applying the Anti-Money Laundering Law, whether in the investigation, prosecution, or trial of criminal acts of corruption, has not been optimal, so it has not supported efforts to recover state losses.